NEUROPSYCHOPEDAGOGICAL STRATEGIES FOR TEACHING AND LEARNING LIBRAS IN INCLUSIVE EDUCATION CONTEXTS - de Maria Silva de Andrade, Conceição; Maria Jucileide da Silva, Kimlêdalee; Jucilene Silva G de Sousa, Maria (Revista Gênero e Interdisciplinaridade, 2025)
Inclusive education for deaf students in Brazil relies primarily on Brazilian Sign Language (Libras), which is considered essential to the communication, identity, and culture of this community. This article is a systematic literature review, with information updated through 2025, focusing on neuropsychopedagogical strategies. The objective was to analyze effective methods for teaching and learning Libras, aiming to improve cognitive development and reduce learning problems for deaf students, contributing to a more complete education tailored to their needs. The research used a detailed search of academic databases, using keywords such as "Libras," "Neuropsychopedagogy," "deafness," "cognitive development," and "executive functions." The results show a strong interest in interventions that combine neurological and pedagogical knowledge to teach Libras. These approaches are based on diagnostic assessment and the development of teaching strategies that strengthen important cognitive functions, such as attention, memory, and planning, all of which are fundamental to understanding and mastering the language. It is concluded that the combination of Neuropsychopedagogy and Libras teaching methods can generate significant advances in deaf education. This combination can create more inclusive, appropriate, and effective learning environments tailored to the needs of these students. However, to ensure the effectiveness and applicability of these approaches, more practical, evidence-based research is needed to validate and improve the use of these strategies in the Brazilian educational context, fostering their efficient application and significant benefits.